The right to religious expression in Europe and Ireland - Downey, Gerard Cillian (Trinity College (Dublin, Ireland). School of Law, 2015)
This thesis explores the meaning of the right to religious expression in Europe and Ireland. As the contemporary legal environment has sought to re-characterise its relationship with religion, this thesis attempts to objectively appraise the substance of the right so as to give effect to the guarantees upon which it is founded. Through an analysis of the nature of religious belief and manifestation this thesis considers the consequences of religious expression and considers upon what legal basis it can be limited but also provided for.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin.